2014
DOI: 10.7314/apjcp.2014.15.18.7971
|View full text |Cite
|
Sign up to set email alerts
|

CCNA1 Promoter Methylation: a Potential Marker for Grading Papanicolaou Smear Cervical Squamous Intraepithelial Lesions

Abstract: Background: From our previous study, we established that cyclin A1 (CCNA1) promoter methylation is strongly correlated with multistep progression of HPV-associated cervical cancer, suggesting potential use as a diagnostic maker of disease. Objectives: The purpose of the present study was to assess the prevalence of CCNA1 promoter methylation in residual cervical cells isolated from liquid-based cytology that underwent hrHPV DNA screening for cervical cancer, and then to evaluate this marker for diagnostic accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
3
28
1
Order By: Relevance
“…Consistent with previous findings, the CCNA1 and TERT promoter regions showed significantly increased methylation (24–28% increase in β, p  < 0.004) in NIKS-16 cells compared to NIKS cells (Table S3) 10, 13, 14, 23 . However, NIKS-18 cells did not show consistent changes in CCNA1 and TERT promoter methylation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous findings, the CCNA1 and TERT promoter regions showed significantly increased methylation (24–28% increase in β, p  < 0.004) in NIKS-16 cells compared to NIKS cells (Table S3) 10, 13, 14, 23 . However, NIKS-18 cells did not show consistent changes in CCNA1 and TERT promoter methylation.…”
Section: Resultssupporting
confidence: 91%
“…Consistently, the HPV E7-DNMT1 complex induces hypermethylation of the tumor suppressor cyclin A1 ( CCNA1 ) promoter, an epigenetic marker strongly correlated with HPV-associated malignancy 13, 14 . Further, our recent work has revealed that the chemokine CXCL14 is significantly downregulated by E7-directed promoter hypermethylation 15 .…”
Section: Introductionmentioning
confidence: 86%
“…We have previously reported that methylation of the CCNA1 promoter was largely elevated in ~93% of cervical cancer cases, whereas the promoter remains unmethylated in normal counterparts . In addition, other studies recommended that the CCNA1 promoter methylation status be used as the optimal molecular marker for distinguishing between normal/low‐grade squamous intraepithelial neoplasia and high‐grade squamous intraepithelial neoplasia cancer lesions . Moreover, we also observed a significant correlation between the integrated form of HPV infection and CCNA1 promoter methylation .…”
supporting
confidence: 62%
“…(17) In addition, other studies recommended that the CCNA1 promoter methylation status be used as the optimal molecular marker for distinguishing between normal ⁄ low-grade squamous intraepithelial neoplasia and high-grade squamous intraepithelial neoplasia cancer lesions. (18,19) Moreover, we also observed a significant correlation between the integrated form of HPV infection and CCNA1 promoter methylation. (20) Interestingly, the study by Weiss et al found a significant correlation between HPV-related head and neck cancer and CCNA1 methylation.…”
mentioning
confidence: 54%
“…In both cervical and endometrial cancer, specific genes involved in various pathways are known to be methylated. In cervical cancer, these genes include tumor protein p73, fragile histidine triad (FHIT), death-associated protein kinase 1 and PRDI-BF and RIZ domain containing 14 in the apoptotic pathway; cyclin A1 (CCNA1) and double C2-like domain β in the cell cycle; adenomatous polyposis coli (APC) and secreted frizzled-related protein (SFRP) in the Wnt/β-catenin pathway; Fanconi anemia, complementation group F, O-6-methylguanine-DNA methyltransferase, human MutL homolog 1 (hMLH1) and CCNA1 in DNA repair; FHIT, retinoic acid receptor-β and myelin and lymphocyte in the cell growth pathway; and CXC chemokine receptor 4 and cell adhesion molecule 1, which are involved in cell adhesion (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In endometrial cancer, the following genes are methylated: APC, caspase-8, checkpoint with forkhead-associated and ring finger, E-cadherin, hMLH1, p73, progesterone receptor, phosphatase and tensin homologue deleted on chromosome 10, Ras association domain family 1 isoform A and thrombospondin 2 .…”
Section: Introductionmentioning
confidence: 99%